USING MIXED FODDERS WITH DIFFERENT LEVELS OF LYSINE IN OSTRICHES FEEDING - Федорук, Н. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
Current state of ostrich production in Ukraine requires evidence-based recommendations on the amino acidnitrition og poultry. African ostrich females eggs productivity depends on the content of essential amino acids in the feed .Lysine is an essential element of theamino acids contained in fodder. There has been experimentally determined the lysine optimal content in the composition of animal feed for Africanostriches during oviposition. The highest egg productivity was found in the experimental group of birds that consuming feed with lysine content of 1.1 %. Iaying egg productivity index per female was higher than in the control variantby 8.0 %. Gross ostrich eggs production from females consuming feed containing 1.1 % of lysine was different from that of the control by 7.9 %. No significant difference was found between the eggs weigh obtained from female ostriches consuming feed containing 1.1 and 1.2 % of lysine.